Surface-ocean dynamics during eccentricity minima: a comparison between interglacial Marine Isotope Stage (MIS) 1 and MIS 11 on the Iberian Margin - Palumbo, Eliana (2020)
Understanding interglacial climate variability is a key issue in the scientific community. Here we compared records from Marine Isotope Stage (MIS) 11 to those from MIS 1 (Holocene) as they are perceived to be possible analogs. Our study on the Iberian Margin, a key area to investigate surface dynamics in the Atlantic Ocean, incorporates coccolithophore assemblage and alkenone data of core MD03-2699 and their statistical analyses. Evaluating similarities between MIS 11 and MIS 1 depends on the way the two MIS are being aligned, i.e. at the deglaciation or based on the precession signal. During the deglaciation of either MIS 12 or MIS 2, the Iberian Margin was affected by abrupt decreases in SST and in coccolithophores' paleoproductivity caused by the arrival of subpolar surface waters. Just prior to the decline, in both the intervals, the Portugal Current affected the studied site, although a possible difference in upwelling strength is here suggested and related to more intense westerlies during the last glacial than the late MIS 12. Similar surface-ocean dynamics occurred at the onset of both MIS 11 and MIS 1 as indicated by the prevalence of the Iberian Poleward Current and sometimes the Azores Current, although the subtropical waters were more oligotrophic during the MIS 2 deglaciation than the MIS 12 one. Synchronizing our records according to the precession cycles aligns the early-to-mid Holocene with the second, warmer phase of MIS 11c. During both these intervals, the western Iberian Margin was mainly affected by the Iberian Poleward Current that transported more temperate-warm, mesotrophic surface waters during MIS 11c than during the early-to-mid Holocene. During the early to mid-Holocene the Iberian Margin endured incursions of colder surface waters that did not occur during MIS 11c allowing us to hypothesize that the studied site experienced, from a paleoceanographic point of view, a more stable period during MIS 11c than the early Holocene. Finally, spectral analysis suggests the role of full, half and fourth precession components in driving surface-ocean variability during MIS 11 and during the last 24 kyr BP.